2020
DOI: 10.1177/0706743720919278
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Trauma Exposure and Physical Conditions among Public Safety Personnel: Associations entre l’exposition à un traumatisme et les problèmes physiques chez le personnel de la santé publique

Abstract: Background: Trauma exposure is associated with adverse health-related correlates, including physical comorbidities, and is highly prevalent among public safety personnel (PSP). The current study (1) examined the association between context of index trauma exposure (part of job vs. other) and physical conditions and (2) established the prevalence of physical conditions according to PSP category (e.g., police, paramedic) and index trauma type (e.g., serious accident, physical assault) in a large Canadian sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 67 publications
(93 reference statements)
2
13
0
1
Order By: Relevance
“…CWs described their family physician as a primary contact for help-seeking, which is consistent with previous research results from among other populations, such as PSP and the general public [ 47 ]. Our current preliminary results with CWs are consistent with previous research on PSP [ 48 , 49 ], in that symptoms of psychological distress can present with physical symptoms (e.g., migraines). Future research on PSP who present with physical symptoms may provide important insights into mental health disorders and suicidal behaviours.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CWs described their family physician as a primary contact for help-seeking, which is consistent with previous research results from among other populations, such as PSP and the general public [ 47 ]. Our current preliminary results with CWs are consistent with previous research on PSP [ 48 , 49 ], in that symptoms of psychological distress can present with physical symptoms (e.g., migraines). Future research on PSP who present with physical symptoms may provide important insights into mental health disorders and suicidal behaviours.…”
Section: Discussionsupporting
confidence: 91%
“…Some of our participating CWs reported feeling less understood or even misunderstood by the mental health professionals who offer help, which is consistent with previous research among police [ 11 , 49 , 50 ] and other PSP [ 47 ]. Participating CWs appeared to understand that their work environment (e.g., prison, community, supporting prisoners/probationers/parolees), organisational culture, and frequent PPTE exposures (e.g., violence, abuse, suicidal behaviours of others) underscore the importance of cultural competence for perceiving psychological services as potentially effective [ 42 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Addressing a conspicuous absence of similar research in Canada, a recent national survey of Public Safety Personnel (PSP) found that 1 in 4 participating paramedics screened positive for PTSD, 1 in 3 for major depressive disorder, and 1 in 3 for an anxiety disorder, with nearly half screening positive for any one mental disorder [9] and more frequent positive screens observed among women paramedics. Related research has also suggested that exposure to potentially psychologically traumatic events [10][11][12][13][14][15][16]; symptoms consistent with chronic pain, [17] clinical insomnia [18] and alcohol use disorder [9]; suicidal ideation, planning, and attempts [19]; and a history of adverse childhood experiences [20] are prevalent among paramedics, again varying across demographic categories, including gender. The downstream consequences are potentially significant, and can include lost time from work [21], family hardship [22], reduced quality of life [23][24][25][26], and suicidality [7,27], all of which can contribute to burnout [6,28], workplace incivility [29,30], attrition [31] and potentially compromise patient care [32].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis estimated prevalence rates of 11% for PTSD, 15% for depression, 15% for anxiety, and 27% for general psychological distress among EMS workers [ 4 ]. In addition to mental health problems, meta-analyses have highlighted the negative health impacts of PTSD on physical well-being in adults [ 5 ] and among first responders specifically [ 6 , 7 ]. Repercussions are also felt at the organizational level (e.g., increased sick leaves, lowered operational performance; [ 8 , 9 ]).…”
Section: Introductionmentioning
confidence: 99%